2004
DOI: 10.1161/01.cir.0000142052.03565.87
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Ionic Remodeling Induced by Atrial Tachycardia in the Presence of Congestive Heart Failure

Abstract: Background-Atrial fibrillation (AF) and congestive heart failure (CHF) produce discrete forms of atrial ionic remodeling.The in vivo effects of atrial tachycardia (AT) remodeling are altered by CHF. This study evaluated underlying mechanisms at the level of ionic remodeling. Methods and Results-We studied 4 groups of dogs: (1) unpaced controls (CTLs); (2) CHF caused by 2-week ventricular tachypacing (VTP, 240 bpm); (3) AT (400 bpm ϫ7 days); and (4) CHFϩAT (2-week VTP with AT for the last 7 days). CHF and CHFϩA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 33 publications
9
68
0
1
Order By: Relevance
“…Open chest study was performed as previously described. 12 On study days, dogs were anesthetized (morphine 2 mg ⅐ kg Ϫ1 subcutaneous, ␣-chloralose 120 mg ⅐ kg Ϫ1 intravenous load, 29.25 mg ⅐ kg Ϫ1 ⅐ h Ϫ1 infusion) and mechanically ventilated. Right atrial effective refractory period was measured at basic cycle lengths of 150, 200, 250, 300, and 360 ms with 10 basic stimuli (S1) and a second stimulus (S2) with 5-ms decrements (all pulses twice-threshold, 2 ms).…”
Section: Animal Modelmentioning
confidence: 99%
“…Open chest study was performed as previously described. 12 On study days, dogs were anesthetized (morphine 2 mg ⅐ kg Ϫ1 subcutaneous, ␣-chloralose 120 mg ⅐ kg Ϫ1 intravenous load, 29.25 mg ⅐ kg Ϫ1 ⅐ h Ϫ1 infusion) and mechanically ventilated. Right atrial effective refractory period was measured at basic cycle lengths of 150, 200, 250, 300, and 360 ms with 10 basic stimuli (S1) and a second stimulus (S2) with 5-ms decrements (all pulses twice-threshold, 2 ms).…”
Section: Animal Modelmentioning
confidence: 99%
“…In addition, tachycardia-related remodeling is altered by concomitant heart failure, so that tachycardia-induced ionic remodeling in a pathological substrate may differ from what is seen in the normal heart, as in experimental paradigms. 45 …”
Section: Study Limitationsmentioning
confidence: 99%
“…A prominent feature of the electrical remodeling associated with AF is abbreviation of the effective refractory period (ERP) favoring reentry, primarily due to shortening of atrial action potential duration (APD) (9,10). Numerous studies have demonstrated that increased inward-rectifier K + current (I K1 ), along with increased expression of the principal underlying subunit KCNJ2 mRNA and its encoded Kir2.1 protein, is a prominent feature of AF-related atrial electrical remodeling (10)(11)(12)(13)(14)(15)(16)(17). I K1 is the key K + current responsible for setting the resting membrane potential, controlling cardiac excitability, and modulating latephase repolarization and APD in cardiac cells.…”
Section: Introductionmentioning
confidence: 99%